Catalytic Asymmetric Synthesis of Mixed 3, 3′‐Bisindoles and Their Evaluation as Wnt Signaling Inhibitors1. Issue 9 (25th January 2013) - Arai, Takayoshi; Yamamoto, Yushi; Awata, Atsuko; Kamiya, Kentaro; Ishibashi, Masami; Arai, Midori A.
<x xml:space="preserve">Abstract</x> TOP class: The first efficient catalytic asymmetric coupling reaction of indoles with isatin‐derived nitroalkenes was accomplished by using a complex consisting of a chiral imidazoline aminophenol ligand (1; see scheme) and Cu(OTf)2. Biological activity of the newly formed chiral 3, 3′‐bisindoles was also confirmed in a Wnt signaling inhibitory assay.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>